Influence of aluminium coagulants composition on colloidal characteristics of humic substances dispersions - Zyhmant, Alesia V.; Savitskaya, Tatsiana A.; Tsyhankova, Nadzeia G.; Hrynshpan, Dzmitry D. (Journal of the Belarusian State University. Chemistry, 2017)
The effect of aluminium coagulants composition on colloidal characteristics of humic substances dispersions (diameter, particle size distribution, density and sedimentation rate of aggregates) was investigated by using of laser diffraction method. Aggregates shape and structure were characterized by the experimentally determined fractal dimension values in the comparison with computer simulation data. The mixed aggregates size in the humic substances dispersions was founded to increase in the case of aluminium sulphate as a coagulant according to the aluminium hydroxide dispersion when alone. Otherwise, the density of mixed aggregates is lower than for the aggregates in aluminium hydroxide dispersion. In the case of pentahydroxodialuminium chloride, the reverse relationships were observed.